2019
DOI: 10.1111/cea.13323
|View full text |Cite
|
Sign up to set email alerts
|

Rush desensitization with a single antigen induces subclinical activation of mast cells and protects against bystander challenge in dually sensitized mice

Abstract: Background: Rush desensitization can provide short-term tolerance to individuals who are allergic to certain medications in instances where other therapeutic interventions are limited. While rush desensitization (DS) is typically successful in preventing adverse type I hypersensitivity reactions, the mechanism of allergic protection remains unknown. Given the rise in prevalence of individuals displaying multiple allergies, understanding the impact of rush DS on "bystander" allergens, or additional allergens to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…We speculate that the effects we observed on mast cells have broader implications for allergic disease. Depletion or exhaustion of mast cells through repeated degranulation could potentially serve as a mechanism of protection for other type I hypersensitivity reactions and for achieving tolerance during rush desensitization . Future studies will focus on the mechanisms by which chronic helminth infection reduces mast cell numbers and mast cell granularity and explore whether mast cells become “exhausted” and exhibit endoplasmic reticulum stress following chronic activation.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the effects we observed on mast cells have broader implications for allergic disease. Depletion or exhaustion of mast cells through repeated degranulation could potentially serve as a mechanism of protection for other type I hypersensitivity reactions and for achieving tolerance during rush desensitization . Future studies will focus on the mechanisms by which chronic helminth infection reduces mast cell numbers and mast cell granularity and explore whether mast cells become “exhausted” and exhibit endoplasmic reticulum stress following chronic activation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a second study did not find a reduction in surface IgE or in the signal transduction ability of the high‐affinity IgE receptor (FcεRI), but instead found that reorganization of the actin cytoskeleton in desensitized mast cells led to impaired Ca 2+ signalling and prevention of mast cell degranulation 54 . A recent study using a cutaneous model of local anaphylaxis in dual‐sensitized mice showed that desensitization to one allergen conferred protection when challenged to the second allergen 55 . This suggests that early subclinical degranulation of mast cells plays an important role in desensitization and, like basophils, probably provides bystander protection upon exposure to other allergens.…”
Section: During Oitmentioning
confidence: 99%
“…In a study by Killoran and colleagues, the authors used a mouse model to investigate the potential of rush desensitization, a process where short‐term exposure to an allergen can provide a window of tolerance, to protect against diverse allergens. Although rush desensitization with a single model allergen resulted in sustained subclinical degranulation of mast cells, mice were then also protected against a second, unrelated, model allergen 54 . These data, although needing further investigation, highlight a potentially valuable future intervention approach whereby poly‐sensitized allergic individuals might be afforded a window of tolerance against multiple allergens.…”
Section: Basic Mechanisms Underpinning Allergymentioning
confidence: 93%
“…Although rush desensitization with a single model allergen resulted in sustained subclinical degranulation of mast cells, mice were then also protected against a second, unrelated, model allergen. 54 These data, although needing further investigation, highlight a potentially valuable future intervention approach whereby poly-sensitized allergic individuals might be afforded a window of tolerance against multiple allergens.…”
Section: Mast Cellsmentioning
confidence: 99%